Electrode assembly and battery

By designing a plurality of first convex portions on the electrode sheet of the battery electrode assembly and adding a softener, the problem of difficulty in entering the electrolyte is solved, and the charging and discharging cycle performance and safety of the battery are improved.

CN119581565AActive Publication Date: 2025-03-07NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202411786739.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

In existing batteries, the winding electrode assembly makes it difficult for the electrolyte to enter, resulting in insufficient electrolyte and poor infiltration, affecting the charging and discharging cycle performance of the battery, and lithium excretion may occur, affecting the safety of the battery.

Method used

An electrode assembly is designed, wherein at least one electrode sheet has a plurality of first convex portions. By adding a softener to the active material layer, the flexibility of the electrode sheet is improved, and a raised structure is formed in the thickness direction of the electrode sheet to improve the wetting effect of the electrolyte.

Benefits of technology

By increasing the flexibility of the electrode assembly and forming a raised structure, the wetting effect of the electrolyte is improved, the charging and discharge cycle performance of the battery is improved, and the safety of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581565A_ABST
    Figure CN119581565A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode assembly and a battery. The electrode assembly comprises a plurality of pole pieces and an isolating membrane arranged between two pole pieces with opposite polarities, and at least one pole piece is provided with a plurality of first convex parts; the pole piece comprises a current collector and an active material layer arranged on the surface of the current collector, the first convex part is formed by bending a part of the current collector and a part of the active material layer towards the same side of the pole piece, the height of the first convex part is H1, and H1 is more than or equal to 20 microns and less than or equal to 80 microns; the active material layer comprises a softener, the softener is selected from at least one of organic silicon, fatty acid salt and quaternary ammonium salt, based on the total weight of the active material layer, the weight percentage of the softener is A, and A is larger than or equal to 0.01% and smaller than or equal to 0.4%. In the application, the softening agent is added into the active material layer to improve the overall flexibility of the pole piece 300, so that the active material layer at the first convex parts does not generate microcracks while the height of the first convex parts is higher, further, an electrode assembly capable of meeting the use requirements can be conveniently processed, and the electrolyte infiltration effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrode assembly and a battery. Background Art

[0002] At present, the electrode assembly inside the secondary battery adopts a winding structure. After winding, the electrode assembly needs to be hot-pressed and fixed to prevent it from moving or puncturing the outer packaging after being loaded into the outer packaging. However, the wound electrode assembly does not allow the electrolyte to easily enter the electrode assembly, which can easily lead to problems such as insufficient electrolyte and poor infiltration, and ultimately lead to the deterioration of the electrode interface, affecting the battery's charge and discharge cycle performance, and even lithium deposition, affecting battery safety. Summary of the invention

[0003] The inventors found that there would be extrusion between the layers of the electrode assembly, especially during the battery charging and discharging process, the expansion and extrusion of the electrode assembly would be further aggravated, resulting in insufficient electrolyte between the layers of the electrode assembly, poor wetting, prone to interface deterioration, and even abnormal conditions such as poor wetting and cycle failure.

[0004] The embodiments of the present application provide an electrode assembly and a battery, which can improve the problem of poor electrolyte infiltration in the battery.

[0005] In a first aspect, an embodiment of the present application provides an electrode assembly, the electrode assembly comprising a plurality of pole pieces and an isolation membrane disposed between two pole pieces with opposite polarities, wherein at least one pole piece has a plurality of first protrusions.

[0006] The pole piece includes a current collector and an active material layer arranged on the surface of the current collector, the first protrusion is formed by a portion of the current collector and a portion of the active material layer protruding toward the same side of the pole piece, the height of the first protrusion is H1, and H1 satisfies: 20μm≤H1≤80μm; the active material layer includes a softener, and the softener is selected from at least one of silicone, fatty acid salt, and quaternary ammonium salt. Based on the total weight of the active material layer, the weight percentage of the softener is A, and A satisfies: 0.01%≤A≤0.4%.

[0007] Based on the electrode assembly of the embodiment of the present application, the height H1 of the first protrusion is in the range of 20μm≤H1≤80μm, and the first protrusion can provide good support to improve the wetting effect of the electrolyte. The weight percentage A of the softener is in the range of 0.01%≤A≤0.40%. The softener can increase the flexibility of the active material layer, prevent the active material layer from easily breaking, and make the electrode sheet easy to bend to form the first protrusion.

[0008] In some embodiments, the electrode assembly satisfies at least one of the following conditions:

[0009] (1) If A satisfies: 0.01% ≤ A ≤ 0.10%, then H1 satisfies: 20 μm ≤ H1 ≤ 40 μm;

[0010] (2) If A satisfies: 0.10% < A ≤ 0.20%, then H1 satisfies: 40 μm < H1 ≤ 60 μm;

[0011] (3) If A satisfies: 0.20% < A ≤ 0.40%, then H1 satisfies: 60 μm < H1 ≤ 80 μm.

[0012] Based on the above embodiments, the softener can improve the overall flexibility of the electrode sheet, and while achieving a higher height of the first convex portion, reduce the damage to the electrode sheet, prevent microcracks from occurring in the active material layer at the first convex portion, have no side effects on the processing process, and thus facilitate the processing of an electrode assembly that can meet the usage requirements and improve the electrolyte infiltration effect.

[0013] In some embodiments, the silicone is selected from at least one of methyl silicone resin, phenyl silicone resin, vinyl silicone resin, and silicone rubber; the fatty acid salt is selected from at least one of aluminum stearate, magnesium stearate, aluminum isooctanoate, and magnesium isooctanoate; the quaternary ammonium salt is selected from at least one of long-chain quaternary ammonium salts, short-chain quaternary ammonium salts, aliphatic quaternary ammonium salts, and aromatic quaternary ammonium salts.

[0014] In some embodiments, the active material layer includes a first binder, and based on the total weight of the active material layer, the weight percentage content of the first binder is B; the electrode assembly satisfies at least one of the following conditions:

[0015] (1) If B satisfies: 0.8% ≤ B ≤ 1.6%, then H1 satisfies: 20 μm ≤ H1 ≤ 40 μm;

[0016] (2) If B satisfies: 1.6% < B ≤ 2.4%, then H1 satisfies: 40 μm < H1 ≤ 80 μm.

[0017] Based on the above embodiments, during the process of the active material layer of the corner section and the current collector being bent together to form the first convex portion, the active material layer has good ductility and is not prone to cracking, thereby improving the yield rate during the winding process of the electrode sheet and the safety of the battery. Moreover, the content of the first binder is appropriate, preventing the excessive content of the first binder from reducing the energy density of the battery.

[0018] In some embodiments, the first binder is selected from at least one of polyvinylidene fluoride, polyvinyl fluoride, polyvinyl alcohol, polystyrene, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, polyvinyl acetate, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, and polytetrafluoroethylene.

[0019] In some embodiments, the tap density of the active material layer is ρ, 3.6 g / cm 3≤ρ≤4.35g / cm 3 .

[0020] Based on the above embodiments, the active material layer can have good toughness and is not prone to brittle fracture, while the battery has a suitable energy density.

[0021] In some embodiments, the pole piece further includes a primer layer, which is disposed between the active material layer and the current collector. The primer layer includes a primer material, which is selected from at least one of an inorganic oxide and a carbon-containing material.

[0022] In some embodiments, the unit weight of the primer layer is n, and the electrode assembly satisfies at least one of the following conditions:

[0023] (1) η satisfies: 0.5mg / 1540.25mm 2 ≤η≤2.0mg / 1540.25mm 2 , then H1 satisfies: 20μm≤H1≤40μm;

[0024] (2) η satisfies: 2.0 mg / 1540.25 mm 2 ≤η≤4.0mg / 1540.25mm 2 , then H1 satisfies: 40μm≤H1≤80μm.

[0025] Based on the above embodiments, the adhesion between the current collector and the active material layer can be improved, and thus when processing the first protrusion, the adhesion between the active material layer of the first protrusion and the current collector is stronger, reducing the generation of microcracks and powder loss.

[0026] In some embodiments, the straight portion has a second convex portion, which is formed by bending another portion of the current collector and another portion of the active material layer toward the same side of the pole piece, and the height of the second convex portion is H2, 5μm≤H2≤40μm.

[0027] Based on the above embodiment, the second convex portion provided on the straight portion can also provide good support for the isolation membrane, so that the electrolyte can smoothly enter the gap between the straight sections of the straight portion, thereby improving the electrolyte infiltration effect and improving the liquid retention amount.

[0028] In some embodiments, the radius of the inner surface of the first protrusion is R1, the radius of the inner surface of the second protrusion is R2, R1=R2, 0.3mm≤R2≤10.0mm.

[0029] Based on the above embodiment, the heights of the first and second protrusions formed by processing are within a suitable range, and both the first and second protrusions have a suitable elongation rate, so that the first protrusion can provide good support for the isolation membrane and is not easily deformed.

[0030] In some embodiments, the straight portion has a first thickness L1 in the first direction; two corner portions are arranged at opposite ends of the straight portion in a second direction perpendicular to the first direction, and the corner portion has a second thickness L2 in the second direction; each circle of pole pieces includes two straight sections arranged opposite to each other along the first direction and two corner sections arranged at both ends of the straight section along the second direction; the pole piece has a tail end arranged corresponding to the straight section of the outermost circle pole piece, and all the straight sections and tail ends stacked in the first direction form a straight portion; the first thickness L1 is the thickness of the straight portion passing the tail end in the first direction; all the corner sections located on the same side of the straight section in the second direction form a corner portion, and the second thickness L2 is the thickness of the corner portion passing the midpoint of the line connecting the two ends of a corner section of the innermost layer in the second direction. The electrode assembly satisfies at least one of the following conditions:

[0031] (1) The number of windings of the electrode sheet of the electrode body is an even number, and L1 and L2 satisfy: 1.5≤L1 / L2≤2.2; or,

[0032] (2) The number of winding turns of the pole piece of the electrode body is an odd number, and L1 and L2 satisfy: 1.5≤L1 / L2≤2.4.

[0033] Based on the above embodiments, the tension and interlayer extrusion force on the straight section and the corner section are appropriate, so that the first convex portion and the second convex portion can play a good supporting role, are not easily deformed, and improve the electrolyte infiltration effect.

[0034] In some embodiments, 1 mm ≤ L1 ≤ 20 mm, 0.5 mm ≤ L2 ≤ 10 mm.

[0035] Based on the above embodiments, it is convenient to select the first thickness L1 of the straight part and the second thickness L2 of the corner part to be appropriate relative to the height H1 of the first convex portion, so as to prevent the straight section of the straight part from pulling the corner section of the corner part, thereby preventing excessive squeezing of the first convex portion, so as to maintain good supporting stability of the first convex portion, and to make the gap between the isolation membrane of the corner part and the corner section appropriate, which can not only meet the electrolyte infiltration requirements, but also prevent the gap from being too large, resulting in the overall size of the corner part being too large.

[0036] In a second aspect, the present application provides a battery, comprising a housing and an electrode assembly as described above, wherein the electrode assembly is disposed in an internal space of the housing.

[0037] Based on the electrode assembly and battery of the embodiment of the present application, by adding a softener to the active material layer, and selecting the height H1 of the first protrusion and the weight percentage A of the softener to satisfy 0.01%≤A≤0.40%, 20μm≤H1≤80μm, the softener can improve the overall flexibility of the electrode piece 300. For the structure at the first protrusion, the height of the first protrusion can be higher while reducing the damage to the electrode piece, so that the active material layer at the first protrusion does not produce microcracks, and has no side effects on the processing process, thereby facilitating the processing of an electrode assembly that can meet the use requirements, improving the electrolyte infiltration effect, and improving the battery's charge and discharge cycle performance when the electrode assembly is used in the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0039] Figure 1 This is a schematic diagram of the front view structure of a pole piece in an embodiment of the present application in an unfolded state;

[0040] Figure 2 This is a schematic cross-sectional structural diagram of an electrode assembly according to an embodiment of the present application;

[0041] Figure 3 This is a schematic diagram of a partial cross-sectional structure of a pole piece having a convex portion according to an embodiment of the present application;

[0042] Figure 4 This is a schematic diagram of the main structure of a pole piece having an end clearance area according to an embodiment of the present application;

[0043] Figure 5 This is a schematic diagram of the front view structure of a pole piece having a pole ear area according to an embodiment of the present application;

[0044] Figure 6 This is a schematic diagram of the main structure of a pole piece in which the pole ear area penetrates the pole piece in one embodiment of the present application.

[0045] Reference numerals:

[0046] 20. Electrode body; 21. Straight section; 22. Corner section; 40. Tab assembly; 50. Isolation membrane; 201. Straight section; 202. Corner section;

[0047] 300. pole piece; 311. convex part; 3111. inner surface; 3112. outer surface; 301. first convex part; 302. second convex part;

[0048] 410, positive electrode sheet; 420, negative electrode sheet;

[0049] 310, convex point area; 320, tab area; 321, tab installation area; 322, protective glue installation area; 330, end avoidance area; 3201, first side boundary; 3202, second side boundary; 3203, bottom boundary; 3204, third side boundary; 3205, fourth side boundary; 331, head avoidance area; 332, end avoidance area;

[0050] 3411, first edge; 3421, second edge; 3431, third edge; 3441, fourth edge;

[0051] 3101, first boundary; 3102, second boundary; 3103, third boundary; 3104, fourth boundary;

[0052] 341, first area; 342, second area;

[0053] X, length direction; Y, width direction; Z, thickness direction. DETAILED DESCRIPTION

[0054] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0055] The inventors discovered that the electrode assembly inside the secondary battery adopts a winding structure, and the electrode assembly needs to be hot-pressed after the pole pieces and the isolation membranes are alternately stacked and wound. There is internal stress inside the electrode assembly, resulting in poor electrolyte wettability. In addition, the electrode assembly will expand during the charge and discharge process, and the interlayer extrusion of the electrode assembly will be further aggravated, resulting in insufficient electrolyte, poor wetting, and ultimately deterioration of the interface at the weak position, and even lithium deposition. In order to solve the above problems, it is necessary to create gaps between battery layers. Currently, there are the following methods for creating gaps: (1) sticking adhesive tape at specific positions of the electrode sheets to support the formation of gaps. This method currently improves the wetting ability, but the presence of the adhesive tape occupies the thickness, which increases the thickness of the electrode assembly and causes a certain loss in the energy density of the battery; (2) applying soluble chemicals to form gaps by evenly applying some glue soluble in electrolyte on the electrode sheets, but the improvement effect is limited and has other side effects on battery performance; (3) thickening the isolation membrane. The isolation membrane has a stronger ability to store electrolyte and improves the wetting effect of the electrolyte, but this method will make the battery thicker and greatly lose energy density.

[0056] The inventors also found that by machining a convex portion on the pole piece, the convex portion plays a supporting role during the winding process, so that a gap is formed between the pole piece layers of the electrode assembly, thereby improving the transmission capacity of the electrolyte inside the electrode assembly and improving the cycle performance of the battery. Based on this, the embodiment of the present application provides an electrode assembly and a battery, and the convex portion of the pole piece is designed to effectively improve the electrolytic infiltration and pole piece interface problems.

[0057] The battery provided in the embodiment of the present application includes an outer package and an electrode assembly disposed in the inner space of the outer package, and an electrolyte filled in the inner space of the outer package. The electrode assembly includes two pole pieces with opposite polarities and a separator, such as Figure 1 As shown, it is a schematic diagram of the main structure of an electrode sheet 300 in an embodiment of the present application in an unfolded state. The electrode sheets 300 have length directions X, width directions Y and thickness directions Z that are perpendicular to each other. The length directions X, width directions Y and thickness directions Z of the two electrode sheets 300 of opposite polarities of the electrode assembly are consistent. The separator 50 is arranged between the two electrode sheets 300 of opposite polarities in the thickness direction Z of the electrode sheets 300. One of the two electrode sheets 300 of opposite polarities is a positive electrode sheet 410, and the other is a negative electrode sheet 420. The separator 50 has insulation properties and is used to separate the positive electrode sheet 410 from the negative electrode sheet 420 to prevent the positive electrode sheet 410 and the negative electrode sheet 420 from short-circuiting.

[0058] At least one of the positive electrode sheet 410 and the negative electrode sheet 420 has a convex portion 311. Specifically, the electrode sheet includes a current collector and an active material layer. The active material layer and the current collector are stacked along the thickness direction Z of the electrode sheet 300, and the active material layer is disposed on the surface of the current collector. The convex portion 311 is formed by a portion of the current collector and a portion of the active material layer protruding toward the same side of the electrode sheet 300 along the thickness direction Z of the electrode sheet 300. The convex portion 311 provides support for the isolation film 50, so that there is a gap between the isolation film 50 and the electrode sheet 300, and the electrolyte infiltration effect is improved.

[0059] The pole piece 300 includes a first surface perpendicular to the thickness direction Z of the pole piece 300. Figure 1 The first surface includes a convex region 310, and a plurality of convex portions 311 are provided in the convex region 310, and there is a gap between the convex region 310 and the edge of the first surface. After the two pole pieces 300 and the isolation film 50 are wound multiple times to form the electrode body 20, the convex portion 311 contacts the isolation film 50 to provide support for the isolation film 50. When the electrode body 20 expands, the convex portion 311 can still support the isolation film 50. The contact area between the convex portion 311 and the isolation film 50 is small, so that there is space between the portion of the pole piece 300 corresponding to the convex region 310 and the isolation film 50 for accommodating electrolyte, thereby preventing abnormal situations such as insufficient electrolyte and poor wetting between the pole piece 300 and the isolation film 50 due to expansion and extrusion.

[0060] like Figure 2 As shown, the isolation film 50 and the two pole pieces 300 are wound multiple times along the length direction X of the pole piece 300 to form the electrode body 20, and the length direction X of the pole piece 300 is the direction in which the pole piece 300 is wound. The electrode body 20 is flat, and the electrode body 20 includes a straight portion 201 and two corner portions 202, and the two corner portions 202 are arranged at opposite ends of the straight portion 201. Specifically, each circle of the pole piece 300 of the electrode body 20 includes two straight sections 21 and two corner sections 22, and the two straight sections 21 are arranged side by side in a direction perpendicular to the plate surface of the straight section 21, and the two straight sections 21 are arranged opposite to each other in a direction perpendicular to the plate surface of the straight section 21, that is, the two straight sections 21 and the two corner sections 22 are connected end to end in sequence. The electrode body 20 has a tail end, and the tail end is formed by a part of the straight section 21 of the outermost circle of the pole piece 300. All the straight sections 21 stacked in the first direction, the tail ends, and the isolation membrane 50 sandwiched between two adjacent straight sections 21 together form a straight portion 201; all the corner sections 22 located on the same side of the straight section 21 in the second direction and the isolation membrane 50 sandwiched between two adjacent corner sections 22 together form a corner portion 202.

[0061] The pole piece 300 has a plurality of convex portions 311, and at least one of the straight section 21 and the corner section 22 has a convex portion 311. Optionally, all the convex portions 311 provided on a single pole piece 300 protrude toward the same side of the pole piece 300 in the thickness direction Z of the pole piece 300. For example, when both the straight section 21 and the corner section 22 have convex portions 311, the convex portion 311 provided on the straight section 21 protrudes toward the side of the winding center of the electrode body 20, and the convex portion 311 provided on the corner section 22 protrudes toward the side where the winding center of the electrode body 20 is located; or, the convex portion 311 provided on the straight section 21 protrudes toward the side away from the winding center of the electrode body 20, and the convex portion 311 provided on the corner section 22 protrudes toward the side away from the winding center of the electrode body 20. Optionally, a portion of the protrusions 311 provided on a single pole piece 300 protrudes toward one side of the pole piece 300 in the thickness direction Z of the pole piece 300, and another portion of the protrusions 311 protrudes toward the other side of the pole piece 300 in the thickness direction Z of the pole piece 300. For example, the protrusions 311 provided on the straight section 21 protrude toward one side of the winding center of the electrode body 20, and the protrusions 311 provided on the corner section 22 protrude toward the side away from the winding center of the electrode body 20; or, the protrusions 311 provided on the straight section 21 protrude toward the side away from the winding center of the electrode body 20, and the protrusions 311 provided on the corner section 22 protrude toward the side of the winding center of the electrode body 20.

[0062] The above is only an exemplary introduction. The present application does not limit the orientation of the protrusion 311 of each pole piece 300 , and the orientation can be selected according to actual needs.

[0063] Due to the internal stress within the electrode body 20 and the expansion of the electrode body 20 during the charge and discharge process of the battery, adjacent two turns of the electrode tabs 300 are prone to extrusion. In particular, the extrusion of the corner segments 22 of adjacent two turns of the electrode tabs 300 is relatively strong, and it is easy to have insufficient gaps, resulting in poor infiltration of the electrolyte. Also, under the action of the extrusion force and internal stress, when the corner segment 22 has a convex portion 311, the convex portion 311 at the corner segment 22 is prone to deformation, and cracks are likely to appear in the active material layer, thereby affecting the cycle performance of the battery.

[0064] The electrode tab 300 has a plurality of convex portions 311, and a part of the convex portions 311 are the first convex portions 301. The corner portion 202 has the first convex portions 301 (specifically, each corner segment 22 has the first convex portions 301). Among them, in the thickness direction Z of the electrode tab 300, the height of the first convex portion 301 is H1, and 20 μm ≤ H1 ≤ 80 μm. In this height range, the first convex portion 301 can provide good support to improve the infiltration effect of the electrolyte.

[0065] The material of the active material layer includes a softening agent, and the softening agent is selected from at least one of silicone, fatty acid salts, and quaternary ammonium salts. Based on the total weight of the active material layer, the weight percentage content of the softening agent is A, and 0.01% ≤ A ≤ 0.40%. In this content range, the softening agent can increase the flexibility of the active material layer, prevent the active material layer from easily breaking, and make the electrode tab 300 easy to bend and form the convex portion 311.

[0066] Since the corner segment 22 is a high-incidence area of bending deformation, therefore, when the height H1 of the first convex portion 301 at the corner segment 22 is larger, the first convex portion 301 supports the separator 50, and the gap between the separator 50 and the electrode tab 300 is larger, and the improvement effect on the infiltration of the electrolyte is better. However, the higher the height of the first convex portion 301, the larger the elongation rate of the electrode tab 300 at the first convex portion 301 or the area covered by the first convex portion 301, the more likely it is to cause the electrode tab 300 at the first convex portion 301 to deform or cause cracks to appear in the active material layer. Based on this, in the implementation of this application, the height H1 of the first convex portion 301 at the corner segment 22 and the weight percentage content A of the softening agent satisfy the following conditional expressions:

[0067] (1) When A satisfies: 0.01% ≤ A ≤ 0.10%, then H1 satisfies: 20 μm ≤ H1 ≤ 40 μm.

[0068] (2) When A satisfies: 0.10% < A ≤ 0.20%, then H1 satisfies: 40 μm < H1 ≤ 60 μm.

[0069] (3) When A satisfies: 0.20% < A ≤ 0.40%, then H1 satisfies: 60 μm < H1 ≤ 80 μm.

[0070] By selecting H1 and A to meet the above ranges, the softener can improve the overall flexibility of the electrode sheet 300. For the structure at the first convex portion 301, while achieving a higher height of the first convex portion 301, the damage to the electrode sheet 300 can be reduced, so that no microcracks are generated in the active material layer at the first convex portion 301, and there are no side effects on the processing process. Furthermore, it is convenient to process an electrode assembly that can meet the usage requirements, improve the electrolyte infiltration effect, and when the electrode assembly is applied to a battery, improve the charge and discharge cycle performance of the battery. Among them, when H1 is lower than the lower limit of 20 μm, the height of the first convex portion 301 is too low, and the supporting ability of the first convex portion 301 for the separator 50 is insufficient. When H1 is higher than the upper limit of 80 μm, the height of the first convex portion 301 is too high, and the first convex portion 301 is prone to deformation under the action of external force. In addition, when A satisfies 0.01% ≤ A ≤ 0.10% and H1 exceeds the upper limit by 40 μm, or when A satisfies 0.10% < A ≤ 0.20% and H1 exceeds the upper limit by 60 μm, cracks are likely to appear in the active material layer at the first convex portion 301 due to insufficient content of the softener; when A satisfies 0.10% < A ≤ 0.20% and H1 is lower than the lower limit by 40 μm, or when A satisfies 0.20% < A ≤ 0.40% and H1 is lower than the lower limit by 60 μm, due to the narrow selectable range of the height of the first convex portion 301, it is impossible to create a sufficient height of the first convex portion 301, resulting in insufficient improvement effect on infiltration and likely deterioration of the charge and discharge cycle performance of the battery.

[0071] In some embodiments, the silicone is selected from at least one of methyl silicone resin, phenyl silicone resin, vinyl silicone resin, and silicone rubber.

[0072] In some embodiments, the fatty acid salt is selected from at least one of aluminum stearate, magnesium stearate, aluminum isooctanoate, and magnesium isooctanoate.

[0073] In some embodiments, the quaternary ammonium salt is selected from at least one of long-chain quaternary ammonium salts, short-chain quaternary ammonium salts, aliphatic quaternary ammonium salts, and aromatic quaternary ammonium salts. For example, the long-chain quaternary ammonium salts are selected from at least one of cetyl dimethyl ammonium bromide, octadecyl dimethyl ammonium bromide, dimethyl dicetyl ammonium bromide, cetyl dimethyl benzyl ammonium chloride, and octadecyl dimethyl benzyl ammonium chloride; the short-chain quaternary ammonium salts are selected from at least one of sodium octanoate, decyl trimethyl ammonium bromide, benzalkonium chloride, and benzalkonium bromide; the aliphatic quaternary ammonium salts are selected from at least one of dodecylamine, hexadecylamine, dodecylpropylamine, and hexadecylpropylamine; and the aromatic quaternary ammonium salts are selected from at least one of aniline, aromatic amine, benzidine, and naphthylamine.

[0074] In some embodiments, the active material layer further includes a first binder. Based on the total weight of the active material layer, the weight percentage content of the first binder is B, and the height H1 of the first convex portion 301 at the corner section 22 and the weight percentage content B of the first binder satisfy the following conditional formula:

[0075] (1) If B satisfies: 0.8% ≤ B ≤ 1.6%, then H1 satisfies: 20 μm ≤ H1 ≤ 40 μm.

[0076] (2) If B satisfies: 1.6% < B ≤ 2.4%, then H1 satisfies: 40 μm < H1 ≤ 80 μm.

[0077] By selecting H1 and B to satisfy the above ranges, the active material layer has good toughness and ductility, making it difficult for microcracks to occur in the active material layer. During the process of bending the active material layer of the corner section 22 together with the current collector to form the first convex portion 301, the active material layer has good ductility and is not prone to cracking, thereby improving the yield rate during the winding process of the pole piece 300 and improving the safety of the battery. In addition, when the weight percentage content B of the first adhesive satisfies the above range, its proportion in the active material layer is appropriate, preventing the excessive content of the first adhesive from reducing the energy density of the battery.

[0078] In some embodiments, the first adhesive is selected from at least one of polyvinylidene fluoride, polyvinyl fluoride, polyvinyl alcohol, polystyrene, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, polyvinyl acetate, polyvinylpyrrolidone, polyethylene ether, polymethyl methacrylate, and polytetrafluoroethylene.

[0079] In some embodiments, the tap density of the active material layer is ρ, 3.6 g / cm 3 ≤ ρ ≤ 4.35 g / cm 3 , for example, ρ can be 3.6 g / cm 3 、3.8 g / cm 3 、4.00 g / cm 3 、4.05 g / cm 3 、4.08 g / cm 3 、4.10 g / cm 3 、4.18 g / cm 3 、4.28 g / cm 3 、4.35 g / cm 3 Or any range between the above two. Within the above range, the active material layer can have good toughness, is not prone to brittle fracture, and at the same time enables the battery to have an appropriate energy density.

[0080] In some embodiments, the thickness of the active material layer is h1, and h1 satisfies: 10 μm ≤ h1 ≤ 500 μm.

[0081] In some embodiments, the pole piece further includes a primer layer, which is disposed between the active material layer and the current collector. The primer layer includes a primer material, which is selected from at least one of an inorganic oxide and a carbonaceous material. The primer layer further includes an adhesive material, which is mixed with the primer material in the primer layer. The primer layer is bonded to the active material layer and the current collector through the adhesive material. The connection stability of the active material layer can be improved by providing the primer layer, and the active material layer can be prevented from peeling off. Among them, the inorganic oxide is selected from at least one of aluminum oxide, titanium oxide, and magnesium oxide, and the carbonaceous material is selected from at least one of graphene, carbon nanotubes, and fluorocarbon. The adhesive material can be selected from the same material as the first adhesive.

[0082] In some embodiments, the unit weight of the primer layer is η, and the height H1 of the first convex portion 301 of the corner section 22 and the unit weight of the primer layer η satisfy the following conditional formula:

[0083] (1) η satisfies: 0.5mg / 1540.25mm 2 ≤η≤2.0mg / 1540.25mm 2 , then H1 satisfies: 20μm≤H1≤40μm.

[0084] (2) η satisfies: 2.0 mg / 1540.25 mm 2 ≤η≤4.0mg / 1540.25mm 2 , then H1 satisfies: 40μm≤H1≤80μm.

[0085] By selecting H1 and η to satisfy the above range, the adhesion between the current collector and the active material layer can be improved, and thus when processing the first protrusion 301, the adhesion between the active material layer of the first protrusion 301 and the current collector is stronger, reducing the generation of microcracks and powder loss.

[0086] In some embodiments, the thickness of the primer layer is h2, and h2 satisfies: 0.5 μm≤h2≤4.0 μm.

[0087] In some embodiments, a portion of the convex portion 311 is a second convex portion 302, and the straight portion 201 has a second convex portion 302. Specifically, the straight segment 21 has a second convex portion 302. Along the thickness direction Z of the pole piece 300, the height of the second convex portion is H2, 5μm≤H2≤40μm, for example, H2 can be 5μm, 10μm, 20μm, 30μm, 5μm, 35μm, 40μm or any range of the above two. By selecting the height H2 of the second convex portion 302 to meet the above range, the second convex portion 302 can provide good support for the isolation membrane 50, so that the electrolyte can smoothly enter the gap between the straight segments 21 of the straight portion 201, improve the electrolyte infiltration effect and improve the liquid retention.

[0088] It should be noted that in the embodiments of the present application, the material composition, thickness and compaction density of the active material layers corresponding to the straight section 21 and the corner section 22 are the same, and the material composition, thickness and unit primer weight of the primer layers corresponding to the straight section 21 and the corner section 22 are the same.

[0089] In some embodiments, the radius of the inner surface of the first convex portion 301 is R1, and the radius R1 is the ball diameter of the inscribed ball D1 of the inner surface of the first convex portion 301. The radius of the inner surface of the second convex portion 302 is R2, and the radius R2 is the ball diameter of the inscribed ball D2 of the inner surface of the second convex portion 302, wherein R1=R2, 0.3mm≤R2≤10.0mm, for example, R2 can be 0.3mm, 2.3mm, 5.5mm, 7.3mm, 8.5mm, 10.0mm. By selecting the radius range of both the first convex portion 301 and the second convex portion 302 to be within the above range, it is convenient to process and form the height of the first convex portion 301 and the second convex portion 302 to be within a suitable range, and it can take into account that the first convex portion 301 and the second convex portion 302 have a suitable elongation, so that the first convex portion 301 can provide good support for the isolation membrane 50 and is not easy to deform.

[0090] In some embodiments, please refer to Figure 2 The straight portion 201 has a first thickness L1 in the first direction, and the first thickness L1 is the thickness of the straight portion 201 passing the end of the tail in the first direction; the corner portion 202 has a second thickness L2 in the second direction, and the second thickness L2 is the thickness of the corner portion 202 passing the midpoint of the line connecting the two ends of a corner segment 22 of the innermost layer in the second direction. L1 and L2 satisfy the following conditional formula:

[0091] (1) The number of winding turns of the electrode sheet of the electrode body is an even number, and L1 and L2 satisfy: 1.5≤L1 / L2≤2.2.

[0092] (2) The number of winding turns of the pole piece of the electrode body is an odd number, and L1 and L2 satisfy: 1.5≤L1 / L2≤2.4.

[0093] By selecting the first thickness L1 of the straight portion 201 and the second thickness L2 of the corner portion 202 to satisfy the above conditional range, the tension and interlayer extrusion force on the straight section 21 and the corner section 22 are appropriate, so that the first protrusion 301 and the second protrusion 302 can play a good supporting role, are not easily deformed, and the electrolyte infiltration effect is improved.

[0094] In some embodiments, the straight portion 201 has a first thickness L1 in the first direction that satisfies: 1mm≤L1≤20mm, for example, L1 may be 1mm, 2mm, 5mm, 8mm, 10mm, 15mm, 20mm or any range thereof. In the above range, it is convenient to select the first thickness L1 of the straight portion 201 and the height H1 of the first convex portion 301 to be within a suitable range, so as to prevent the straight section 22 of the straight portion 201 from pulling the corner section 21 of the corner portion 202, thereby preventing excessive squeezing of the first convex portion 301, so as to maintain good support stability of the first convex portion 301.

[0095] In some embodiments, the corner portion 202 has a second thickness L2 in the second direction that satisfies: 0.5 mm ≤ L2 ≤ 10 mm, for example, L2 can be 0.5 mm, 1 mm, 2 mm, 5 mm, 6 mm, 8 mm, 10 mm or any range of the above two. In the above range, it is convenient to match the second thickness L2 of the corner portion 202 and the height H1 of the first convex portion 301 in a suitable range, so that the gap between the isolation membrane 50 of the corner portion 202 and the corner segment 21 is appropriate, which can not only meet the electrolyte infiltration requirements, but also prevent the gap from being too large, resulting in the overall size of the corner portion 202 being too large.

[0096] In some embodiments, the surface of the active material layer facing away from the current collector forms a first surface, the first surface includes a convex region 310, a convex portion 311 is provided in the convex region 310, the convex region 310 is defined by a convex boundary line, the convex portion 311 of the convex region 310 may be located in the inner area defined by the convex boundary line, and the convex portion 311 may also be inscribed in the convex boundary line. The first surface also includes an end avoidance region 330 and an edge avoidance region, the end avoidance region 330 is connected to the end of the convex region 310 in the length direction X of the pole piece 300 and extends to the edge of the pole piece 300, and the edge avoidance region is provided on one side of the convex region 310 in the width direction Y of the pole piece 300 and extends to the edge of the pole piece 300. The edge avoidance region and the end avoidance region 330 are not provided with a convex portion 311, and after the two pole pieces 300 and the isolation film 50 are wound, the surface of the pole piece 300 corresponding to the edge avoidance region and the end avoidance region 330 can be spaced from the isolation film 50.

[0097] The end avoidance region 330 is disposed at the end of the convex point region 310 in the length direction X of the pole piece 300 and extends to the edge of the pole piece 300, and the end avoidance region 330 also extends to the edge of the pole piece 300 in the width direction Y of the pole piece 300. Figure 4As shown, the end space avoidance area 330 includes at least one of a head space avoidance area 331 and a tail space avoidance area 332. Preferably, the end space avoidance area 330 includes both the head space avoidance area 331 and the tail space avoidance area 332. In the length direction X of the pole piece 300, the head space avoidance area 331 is arranged at one end of the convex point area 310, and the tail space avoidance area 332 is arranged at the other end of the convex point area 310.

[0098] After the two pole pieces 300 and the isolation film 50 are wound, the head air avoidance area 331 can be located in the innermost turns of the electrode body 20, which is convenient for the winding of the electrode body 20 and helps to improve the structural stability of the central area of ​​the electrode body 20. The tail air avoidance area 332 can be located in the outermost turns of the electrode body 20. The tail air avoidance area 332 can serve as a buffer area between the protrusion 311 and the tail end of the electrode body 20, so that the portion of the pole piece 300 corresponding to the end air avoidance area 330 can more smoothly form a constraint on the inner layer structure of the electrode body 20, which helps to improve the packaging stability of the electrode body 20. Especially when the electrode body 20 has a tendency to expand, the tail air avoidance area 332 without the protrusion 311 is used for tailing, which can prevent the tail of the electrode body 20 from slipping due to expansion stress and improve the structural stability of the electrode body 20.

[0099] Specifically, the first surface of the pole piece 300 includes a first edge 3411 and a second edge 3421 that are relatively set in the length direction X of the pole piece 300, and the convex point boundary line of the convex point area 310 includes a first boundary 3101 and a second boundary 3102 that are relatively set in the length direction X of the pole piece 300, the first boundary 3101 corresponds to the first edge 3411, and the second boundary 3102 corresponds to the second edge 3421. The head space avoidance area 331 is formed between the first edge 3411 and the first boundary 3101, and the tail space avoidance area 332 is formed between the second edge 3421 and the second boundary 3102. One end of the isolation membrane 50 is flush with the head space avoidance area 331 or extends out of the head space avoidance area 331 to be sandwiched between two pole pieces 300 with opposite polarities. The pole piece 300 is wound along the length direction X of the pole piece 300 from the head space avoidance area 331 and the isolation membrane 50 to form a flat electrode body 20, that is, the head space avoidance area 331 is located in the inner circle of the electrode body 20, and the tail space avoidance area 332 is located in the outer circle of the electrode body 20. The other end of the isolation membrane 50 extends out of the tail space avoidance area 332 in the winding direction of the pole piece 300 to prevent the isolation membrane 50 from shrinking and causing the two pole pieces 300 with opposite polarities to short-circuit.

[0100] The first surface of the pole piece 300 has an edge avoidance area, which includes a first area 341 and a second area 342. In the width direction Y of the pole piece 300, the first area 341 is connected to one side of the convex area 310, and the second area 342 is connected to the other side of the convex area 310. The first area 341 extends to the edge of the pole piece 300 in a direction away from the second area 342, and the second area 342 extends to the edge of the pole piece 300 in a direction away from the first area 341. That is, the two opposite boundaries of the convex area 310 in the width direction Y of the pole piece 300 are respectively spaced from the corresponding edges of the pole piece 300, thereby preventing the deformation stress when the convex portion 311 is processed in the convex area 310 from causing abnormal deformation such as wavy edges or wrinkles on the edge of the pole piece 300.

[0101] Specifically, the pole piece 300 includes a third edge 3431 and a fourth edge 3441 that are relatively arranged in the width direction Y of the pole piece 300, and the convex point boundary line of the convex point area 310 includes a third boundary 3103 and a fourth boundary 3104 that are relatively arranged in the width direction Y of the pole piece 300, the third boundary 3103 corresponds to the third edge 3431, and the fourth boundary 3104 corresponds to the fourth edge 3441. The first area 341 is formed between the third boundary 3103 and the third edge 3431, and the second area 342 is formed between the fourth boundary 3104 and the fourth edge 3441, and the first area 341 and the second area 342 extend in the length direction X of the pole piece 300 to connect to the end avoidance area 330, that is, the extension line of the first boundary 3101, the extension line of the second boundary 3102, the third boundary 3103 and the first boundary 3104. The three edges 3431 define a first area 341, the extension line of the first boundary 3101, the extension line of the second boundary 3102, the fourth boundary 3104 and the fourth edge 3441 define a second area 342, the extension line of the first boundary 3101, the first edge 3411, the third edge 3431 and the fourth edge 3441 define a head avoidance area 331, the extension line of the second boundary 3102, the second edge 3421, the third edge 3431 and the fourth edge 3441 define a tail avoidance area 332, the convex point area 310 is located in the area defined by the first boundary 3101, the second boundary 3102, the third boundary 3103 and the fourth boundary 3104, and the convex portion 311 can be inscribed in at least one of the first boundary 3101, the second boundary 3102, the third boundary 3103 and the fourth boundary 3104.

[0102] Optionally, the first boundary 3101, the second boundary 3102, the first edge 3411 and the second edge 3421 are parallel to the width direction Y of the pole piece 300, and the third boundary 3103, the fourth boundary 3104, the third edge 3431 and the fourth edge 3441 are parallel to the length direction X of the pole piece 300. At this time, the head avoidance area 331 and the tail avoidance area 332 are each independently rectangular or square, and the first area 341 and the second area 342 are rectangular.

[0103] Optionally, one of the first region 341 and the second region 342 is used to mount the tab assembly 40 of the electrode assembly, such as Figure 4 As shown, exemplarily, the second region 342 is used to install the tab assembly 40 of the electrode assembly, and the convex region 310 is spaced apart from the tab assembly 40. At this time, the convex region 310 is defined by a first boundary 3101, a second boundary 3102, a third boundary 3103 and a fourth boundary 3104.

[0104] Alternatively, if Figure 5 As shown, the first surface also includes a tab area 320 , which extends from the third boundary 3103 toward the side where the fourth boundary 3104 is located. The tab area 320 is used to install the tab assembly 40 of the electrode assembly, and the tab assembly 40 is spaced apart from the bump area 310 . Among them, when the pole lug assembly 40 is installed in the pole lug area 320, its processing method will affect the installation stability of the pole lug assembly 40, as well as the stability of the structure around the pole lug assembly 40, and further affect the stability of the interface of the pole piece 300. For example, when the pole lug assembly 40 is pressed and installed on the pole piece 300 by rolling, the pole lug assembly 40 is pressed together with the area with the protrusion 311, or the distance between the pole lug assembly 40 and the protrusion 311 is too close, which may cause deformation of the protrusion 311 and the existence of indentations. By planning the pole lug area 320 for installing the pole lug assembly 40, the installation of the pole lug assembly 40 is facilitated, the process difficulty is reduced, the installation stability of the pole lug assembly 40 is improved, and the interface stability near the pole lug assembly 40 is improved. The pole lug assembly 40 and the protrusion 311 can also be misaligned in the thickness direction Z of the pole piece 300. When the electrode assembly is applied to a battery, it helps to improve the energy density of the battery.

[0105] Each pole lug area 320 is used to set at least one pole lug assembly 40. For example, the pole lug assembly 40 includes a pole lug and a protective glue. The pole lug and the protective glue can be installed in the same pole lug area 320; or, the pole lug is installed in one of the pole lug areas 320, and the protective glue is installed in another pole lug area 320, wherein the pole lug extends out of the edge of the pole sheet 300 along the width direction Y of the pole sheet, and the protective glue is flush with the edge of the pole sheet 300. The protective glue is used to separate the pole lug corresponding to it from the pole sheet 300 to prevent lithium deposition at the pole lug.

[0106] Alternatively, if Figure 5 As shown, the tab region 320 extends from the fourth boundary 3104 along the width direction Y of the pole piece 300 to the side where the third boundary 3103 is located, and is spaced apart from the third boundary 3103; or, as shown in Figure 6, the tab region 320 extends from the fourth boundary 3104 along the width direction Y of the pole piece 300 through the convex point region 310.

[0107] The electrode sheet 300 of the embodiment of the present application can form at least one of a positive electrode sheet 410 and a negative electrode sheet 420. The current collector of the negative electrode sheet 420 is a negative electrode current collector and the active material layer is a negative electrode active material layer. The current collector of the positive electrode sheet 410 is a positive electrode current collector and the active material layer is a positive electrode active material layer. In addition to the above-mentioned softener and the first adhesive, the negative electrode active material layer also includes a negative electrode active material. In addition to the above-mentioned softener and the first adhesive, the positive electrode active material layer also includes a positive electrode active material.

[0108] The embodiments of the present application have no particular restrictions on the materials of the positive electrode active material, the positive electrode current collector, the negative electrode active material and the negative electrode current collector. Various materials that can be used as positive electrode active materials, positive electrode current collectors, negative electrode active materials and negative electrode current collectors that are well known in the art are applicable to the present application.

[0109] For example, the negative electrode current collector may be at least one of copper foil, aluminum foil, nickel foil or carbon-based current collector; the thickness of the negative electrode current collector may be 1 μm to 200 μm. The negative electrode active material layer may be disposed on one surface or two opposite surfaces of the negative electrode current collector. Further, in the thickness direction Z of the negative electrode sheet 420, the negative electrode active material layer may be coated only on a partial area of ​​the negative electrode current collector. For example, the thickness of the negative electrode active material layer may be 10 μm to 500 μm.

[0110] Exemplarily, the negative electrode active material includes at least one of lithium metal, natural graphite, artificial graphite or silicon-based materials, and the silicon-based material includes at least one of silicon, silicon oxide, silicon carbon compound or silicon alloy. The negative electrode active material layer may also include a conductive agent, and exemplarily, the conductive agent in the negative electrode active material layer may include at least one of carbon black, acetylene black, ketjen black, flake graphite, graphene, carbon nanotubes, carbon fibers or carbon nanowires. Among them, the negative electrode active material layer may also include a second adhesive, and the second adhesive may include at least one of carboxymethyl cellulose CMC, polyacrylate, polyacrylate, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, epoxy resin, polyester resin, polyurethane resin or polyfluorene.

[0111] For example, the positive electrode current collector may be made of aluminum foil, and of course, other positive electrode current collectors commonly used in the art may also be used, and the thickness of the positive electrode current collector may be 1 μm to 200 μm. The positive electrode active material layer may be disposed on one surface or two opposite surfaces of the positive electrode current collector, and further, in the thickness direction Z of the positive electrode sheet 410, the positive electrode active material layer may be coated only on a partial area of ​​the positive electrode current collector, and the thickness of the positive electrode active material layer may be 10 μm to 500 μm.

[0112] Exemplarily, the positive electrode active material includes LiCoO 2 、LiNiO 2 、LiMn 2 O 4 、LiCo 1-y M y O 2 、LiNi 1-y M y O 2 、LiMn 2-y M y O 4 、LiNi x Co y Mn z M 1-x-y-z O 2 , wherein M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, and 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1. Exemplarily, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide or lithium nickel manganese oxide, and the above positive electrode active materials may be doped and / or coated. The positive electrode active material layer also includes a conductive agent, and exemplarily, the conductive agent in the positive electrode active material layer may include at least one of conductive carbon black, acetylene black, Ketjen black, flake graphite, graphene, carbon nanotubes or carbon fibers. Among them, the positive electrode active material layer may also include a third adhesive, and the third adhesive may include at least one of a copolymer of vinylidene fluoride and hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.

[0113] The embodiments of the present application have no particular restrictions on the isolation membrane 50, and various materials known in the art that can be used as the isolation membrane 50 are applicable to the present application. Exemplarily, the isolation membrane 50 includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. Especially polyethylene and polypropylene, they have a good effect on preventing short circuits and can improve the stability of the electrode assembly through the shutdown effect. The thickness of the isolation membrane 50 is in the range of about 3μm to 500μm. The positive and negative ears are made of metal conductive materials.

[0114] The tabs in the embodiments of the present application include positive tabs and negative tabs. The positive tabs are arranged on the positive electrode sheet, and the negative tabs are arranged on the negative electrode sheet. The embodiments of the present application have no special restrictions on the positive tabs, negative tabs and protective glue. Various materials that can be used as positive tabs, negative tabs and protective glue known in the art are applicable to the present application.

[0115] The embodiments of the present application do not have any particular restrictions on the electrolyte. Various materials that can be used as electrolytes known in the art are applicable to the present application. The electrolyte includes lithium salts and non-aqueous organic solvents.

[0116] Illustratively, the lithium salt includes lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium nitrate, lithium methylsulfite.

[0117] Exemplarily, the non-aqueous organic solvent may also include at least one of a carboxylate compound, an ether compound or other organic solvent. The above-mentioned carbonate compound may include but is not limited to at least one of a chain carbonate compound and a cyclic carbonate compound. The above-mentioned chain carbonate compound may include but is not limited to at least one of dipropyl carbonate (DPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate. The present application has no particular restrictions on the mass percentage of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the total mass of the electrolyte, the mass percentage of the non-aqueous organic solvent is 10% to 70%.

[0118] The present application has no particular limitation on the battery packaging bag, which may be any packaging bag known in the art, as long as the purpose of the present application can be achieved.

[0119] The present application does not particularly limit the type of battery, which may include any device that generates an electrochemical reaction. In the present application, the battery may include but is not limited to: a lithium metal battery, a lithium ion battery, a lithium polymer battery or a lithium ion polymer battery, etc.

[0120] The preparation process of the battery of the present application is well known to those skilled in the art, and the present application has no special limitation. For example, it may include but is not limited to the following steps: after installing the positive electrode ear on the positive electrode sheet and the negative electrode ear on the negative electrode sheet, the positive electrode sheet, the isolation film and the negative electrode sheet are stacked in sequence, and they are wound, folded, etc. as needed to obtain an electrode assembly with a wound structure, the electrode assembly is placed in a packaging bag, the electrolyte is injected into the packaging bag and the bag is sealed to obtain a battery; or, the positive electrode sheet, the isolation film and the negative electrode sheet are stacked in sequence, and the four corners of the entire stacked structure are fixed with tape to obtain an electrode assembly with a stacked structure, the electrode assembly is placed in a packaging bag, the electrolyte is injected into the packaging bag and the bag is sealed to obtain a battery.

[0121] The battery of the present application can be used for an electrical device, and the present application does not particularly limit the type of the electrical device, and it can be used for any electrical device known in the prior art. In some embodiments, the electrical device may include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor, etc.

[0122] The present application is further described below by taking a lithium-ion battery as an example and combining specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0123] The following methods are used to test the performance of lithium-ion batteries in various embodiments and comparative examples of the present application:

[0124] (1) 25℃ 1C charge / 0.7C discharge cycle capacity retention test method

[0125] In an environment of 25°C, the lithium-ion battery is charged at a constant current of 1C to the full charge voltage (the maximum design voltage of the lithium-ion battery is 4.5V), and then charged at a constant voltage at the maximum voltage until the current is 0.02C, and then discharged at a constant current of 0.7C until the final voltage is 3.0V, and the discharge capacity of the first cycle is recorded. After that, the above steps are repeated for 1000 charge and discharge cycles, and the discharge capacity of the lithium-ion battery after 1000 charge and discharge cycles is recorded.

[0126] 25° C. 1C charge / 0.7C discharge cycle capacity retention rate=(discharge capacity at the 1000th cycle / discharge capacity at the first cycle)×100%.

[0127] (2) 25℃ cyclic lithium deposition test method

[0128] In an environment of 25°C, the lithium-ion battery is charged at a constant current of 1C to the full charge voltage (the battery design maximum voltage is 4.5V), and then charged at a constant voltage at the maximum voltage until the current is 0.02C, and then discharged at a constant current of 0.7C until the final voltage is 3.0V, and the discharge capacity of the first cycle is recorded. After that, the above steps are repeated for 1000 charge and discharge cycles, and the discharge capacity of the lithium-ion battery after 1000 charge and discharge cycles is recorded.

[0129] After testing at 25°C and 1000 charge and discharge cycles, when the battery is in a fully charged state (the battery is designed for a maximum voltage of 4.5V), it is disassembled to observe whether there is lithium deposition at the negative electrode interface / ear / protective glue.

[0130] (3) Winding process processing quality test method

[0131] The separator is placed between two pole pieces 300 (positive pole piece 410 and negative pole piece 420) with opposite polarities on an integrated winding machine for winding to form an electrode body 20, and an X-Ray device is used to measure the distance M (M>0.1mm is acceptable) of the edge of the negative pole piece 420 of the electrode body 20 exceeding the edge of the positive pole piece 410 in the width direction of the positive pole piece 410, and samples are continuously prepared, and the total number of samples T (the total number is 100) and the number of qualified products N are counted;

[0132] Winding ratio = N / T × 100%.

[0133] (4) Battery energy density test method

[0134] In an environment of 25°C, the lithium-ion battery is charged with constant current at a charging current of 0.5C to the full charging voltage (the battery is designed to have a maximum voltage of 4.5V), and then charged with constant voltage at the maximum voltage until the current is 0.02C, and then discharged with constant current at a discharge current of 0.2C until the final voltage is 3.0V, and the discharge capacity of the first cycle is recorded.

[0135] Battery energy density = first 0.2C discharge capacity * first 0.2C discharge platform voltage / lithium-ion battery volume

[0136] (5) Testing methods for softeners

[0137] The softener content is obtained by measuring the content of specific elements in the sample by ICP (inductively coupled plasma emission spectrometry), and the specific elements include but are not limited to the content of silicon in silicone, metal elements in fatty acid salts, and nitrogen in quaternary ammonium salts.

[0138] (6) Test method for height H1 of convex part

[0139] Take the pole piece at the corner of the battery cell to test the height of the convex part.

[0140] Example 1-1

[0141] (1) Preparation of positive electrode sheet

[0142] The binder sodium carboxymethyl cellulose and the primer material aluminum oxide were mixed in a mass ratio of 3:97, water was added as a solvent, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a primer slurry with a solid content of 40wt%. The primer slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, dried at 85°C, and cold pressed to obtain a primer layer with a single-sided coating thickness of 1μm. The unit primer weight η of the primer layer was 2mg / 1540.25mm 2 .

[0143] The positive electrode active material is lithium cobalt oxide LiCoO 2 , conductive carbon black, first binder polyvinylidene fluoride PVDF, and softener methyl silicone resin are mixed in a mass ratio of 97.5:1.69:0.8:0.01, N-methylpyrrolidone NMP is added as a solvent, and stirred evenly under the action of a vacuum mixer to obtain a positive electrode sheet slurry with a solid content of 75wt%. The positive electrode sheet slurry is evenly coated on the surface of the primer layer, dried at 85°C, and cold pressed to obtain a positive electrode sheet with a single-sided coating of a positive electrode active material layer with a thickness of 95μm.

[0144] After that, the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a positive electrode active material layer coated on both sides. After cutting, a positive electrode sheet with a specification of 74mm×851mm is obtained for use. The compaction density of the positive electrode active material layer is 4.20g / cm 3 .

[0145] (2) Preparation of negative electrode sheet

[0146] The negative electrode active material artificial graphite, the binder styrene-butadiene rubber SBR, and the second binder sodium carboxymethyl cellulose CMC are mixed in a mass ratio of 97.4:1.4:1.2, and then deionized water is added as a solvent, and stirred evenly under the action of a vacuum mixer to obtain a negative electrode sheet slurry with a solid content of 50wt%. The negative electrode sheet slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried and cold pressed at 85°C to obtain a negative electrode sheet with a negative electrode active material layer coated on one side with a thickness of 130μm. After that, the above steps are repeated on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode active material layer coated on both sides. After cutting, a negative electrode sheet with a specification of 76mm×867mm is obtained for standby use, and the compaction density of the negative electrode active material layer is 1.80g / cm 3 .

[0147] (3) Preparation of isolation membrane

[0148] A polyethylene (PE) porous membrane with a thickness of 5 μm was used.

[0149] (4) Preparation of electrolyte

[0150] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1:2 to obtain a base solvent, and then lithium hexafluorophosphate (LiPF 6 ) is dissolved in the above-mentioned basic solvent to obtain an electrolyte. Wherein, based on the total mass of the electrolyte, LiPF 6 The mass percentage is 12.5%.

[0151] (5) Assembly of lithium-ion batteries

[0152] The positive electrode aluminum tab is installed on the edge area of ​​the positive electrode sheet 410 by rolling, the protective adhesive is attached to the edge area of ​​the positive electrode sheet 410, and the negative electrode nickel tab is installed on the edge area of ​​the negative electrode sheet 420 by rolling.

[0153] The positive electrode sheet 410 with the positive electrode tab, the separator 50, and the negative electrode sheet 420 with the negative electrode tab are stacked in order, so that the separator 50 is located between the positive electrode sheet 410 and the negative electrode sheet 420 to play a role of isolation, and then wound to obtain the electrode body 20. The electrode assembly is placed in an outer packaging aluminum plastic film, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and then injected with electrolyte, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, capacity, degassing, trimming and other processes.

[0154] In Example 1-1, the positive electrode sheet has a convex portion, and the convex portion is rolled out on the positive electrode sheet by rolling, and Figure 4 The electrode sheet shown is used as a positive electrode sheet, and in the electrode body 20 formed by winding, the corner section 21 of each circle of the electrode sheet 300 has a first protrusion 301, and the straight section 22 has a second protrusion 302. The parameters of the lithium-ion battery are shown in Table I.

[0155] Table I

[0156] parameter Numeric parameter Numeric H1 20mm A 0.01% H2 10mm B 0.8% ρ <![CDATA[4.2g / cm 3 ]]> η <![CDATA[2mg / 1540.25mm 2 ]]> L1 4.5mm L2 3mm L1 / L2 1.5 R2 3mm h1 95μm h2 0μm

[0157] Examples 1-2 to 1-25 and Comparative Examples 1-1 to 1-6 are the same as Example 1-1 except that the height H1 of the first protrusion 301 and the weight percentage A of the softener are adjusted as shown in Table 1 during the preparation of the positive electrode sheet.

[0158] Examples 1-26 to 1-35 are the same as Example 1-1 except that the type of softener is adjusted as shown in Table 1 during the preparation of the positive electrode plate.

[0159] Examples 1-36 to 1-39 are the same as Example 1-1 except that the compaction density ρ of the active material layer is adjusted as shown in Table 1 during the preparation of the positive electrode sheet.

[0160] The parameters of the lithium-ion batteries of Examples 1-1 to 1-39 and Comparative Examples 1-1 to 1-6 and the performance test results of the lithium-ion batteries are shown in Table 1.

[0161] Table 1

[0162]

[0163]

[0164] According to Examples 1-1 to 1-39 and Comparative Examples 1-1 to 1-6 in Table 1, it can be seen that by adding a softener to the active material layer and selecting the height H1 of the first protrusion 301 of the corner section 22 to satisfy 20μm≤H1≤80μm, the weight percentage A of the softener satisfies 0.01%≤A≤0.40%, the lithium ion battery has good charge and discharge cycle performance, and there is no lithium precipitation during the charge and discharge cycle, and the winding process has a good processing rate. When H1 is lower than the lower limit of 20μm, the height of the first protrusion 301 is too low, the supporting capacity of the first protrusion 301 is insufficient, the gap between the positive electrode sheet 410 and the separator 50 is insufficient, and the charge and discharge cycle performance of the lithium ion battery deteriorates. When H1 is higher than the upper limit of 50μm, the height of the first protrusion 301 is too high, and microcracks are prone to occur in the active material layer, resulting in a decrease in the processing rate of the winding process.

[0165] According to Examples 1-1 to 1-25 and Comparative Examples 1-1 to 1-6 in Table 1, the height H1 of the first convex portion 301 of the corner section 22 and the weight percentage A of the softener satisfy (1) 0.01%≤A≤0.10%, 20μm≤H1≤40μm, or satisfy (2) 0.10% <A≤0.20%,40μm

[0166] Examples 2-1 to 2-16 and Comparative Examples 2-1 to 2-4 are the same as Examples 1-4 except that the height H1 of the first protrusion 301 and the weight percentage B of the first adhesive are adjusted as shown in Table 1 during the preparation of the positive electrode sheet.

[0167] ​The parameters of the lithium-ion batteries of Examples 2-1 to 2-14 and Comparative Examples 2-1 to 2-6 and the performance test results of the lithium-ion batteries are shown in Table 2.

[0168] Table 2

[0169]

[0170] According to Examples 1-4, Examples 2-1 to 2-16, and Comparative Examples 2-1 to 2-4 in Table 2, it can be seen that the height H1 of the first protrusion 301 of the corner section 22 and the weight percentage B of the first adhesive are selected to satisfy (1) 0.8% ≤ B ≤ 1.6%, 20 μm ≤ H1 ≤ 40 μm, or (2) 1.6% <B≤2.4%、40μm

[0171] Examples 3-1 to 3-16 and Comparative Examples 3-1 to 3-4 are the same as Examples 1-4 except that the height H1 of the first protrusion 301 and the unit primer weight η of the primer layer are adjusted as shown in Table 1 in the preparation of the positive electrode plate.

[0172] The parameters of the lithium-ion batteries of Examples 3-1 to 3-16 and Comparative Examples 3-1 to 3-4 and the performance test results of the lithium-ion batteries are shown in Table 3.

[0173] Table 3

[0174]

[0175] According to Examples 1-4, Examples 3-1 to 3-16, and Comparative Examples 3-1 to 3-4 in Table 3, it can be seen that the height H1 of the first convex portion 301 of the corner section 22 and the unit primer weight η of the primer layer are selected to satisfy (1) 0.5 mg / 1540.25 mm 2 ≤η≤2.0mg / 1540.25mm 2 , 20μm≤H1≤40μm, or (2) 2.0mg / 1540.25mm 2 ≤η≤4.0mg / 1540.25mm 2 , 40μm≤H1≤80μm, the lithium-ion battery has better charge and discharge cycle performance, and there is no lithium precipitation during the charge and discharge cycle, and the winding process has a good processing rate.

[0176] ​Examples 4-1 to 4-10 are the same as Example 1-1 except that the winding number of the electrode sheet is adjusted as shown in Table 1 during the assembly of the lithium-ion battery and the first thickness L1 and the second thickness L2 of the electrode body 20 are adjusted.

[0177] The parameters of the lithium-ion batteries of Examples 4-1 to 4-10 and the performance test results of the lithium-ion batteries are shown in Table 4.

[0178] Table 4

[0179]

[0180] It can be seen from Example 1-1, Example 4-1 to Example 4-3, and Example 4-9 to Example 4-10 in Table 4 that when the number of winding turns of the electrode sheet 300 of the electrode body is an even number, L1 and L2 satisfy: 1.5≤L1 / L2≤2.2, the lithium-ion battery has good charge and discharge cycle performance, and there is no lithium deposition during the charge and discharge cycle.

[0181] It can be seen from Examples 4-4 to 4-6 and 4-7 to 4-8 in Table 4 that when the number of winding turns of the electrode sheet 300 of the electrode body is an odd number, L1 and L2 satisfy: 1.5≤L1 / L2≤2.4, the lithium-ion battery has good charge and discharge cycle performance, and there is no lithium deposition during the charge and discharge cycle.

[0182] In Examples 5-1 to 5-7, except that the height H1 of the first protrusion 301 and the height H2 of the second protrusion 302 are adjusted as shown in Table 1 during the preparation of the positive electrode sheet, the rest are the same as in Example 1-1.

[0183] The parameters of the lithium-ion batteries of Examples 5-1 to 5-7 and the performance test results of the lithium-ion batteries are shown in Table 5.

[0184] Table 5

[0185]

[0186] It can be seen from Example 1-1 and Example 5-1 to Example 5-7 in Table 5 that when the height H1 of the first protrusion 301 satisfies 20μm≤H1≤80μm, and the height H2 of the second protrusion 302 satisfies 5μm≤H2≤40μm, the heights of the first protrusion 301 and the second protrusion 302 are matched, so that there is a suitable gap between the layers of the straight part and the corner part for accommodating the electrolyte, and the first protrusion 301 and the second protrusion 302 are not easy to deform, thereby improving the charging cycle performance of the lithium-ion battery and having a good winding advantage during the winding process of the electrode 300.

[0187] The same or similar numbers in the drawings of this embodiment correspond to the same or similar parts; in the description of this application, it should be understood that if the terms "upper", "lower", "left", "right", etc. indicate an orientation or position relationship based on the orientation or position relationship shown in the drawings, it is only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as a limitation on this patent. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0188] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. An electrode assembly, characterized in that: The electrode assembly includes a plurality of electrode plates and a separator disposed between two electrode plates with opposite polarities, wherein at least one of the electrode plates has a plurality of first protrusions; The electrode plate includes a current collector and an active material layer disposed on the surface of the current collector. The first protrusion is formed by the protrusion of a part of the current collector and a part of the active material layer toward the same side of the electrode plate, and the height of the first protrusion is H1; The active material layer includes a softening agent selected from at least one of silicone, fatty acid salt, and quaternary ammonium salt. Based on the total weight of the active material layer, the weight percentage content of the softening agent is A; Wherein, A satisfies: 0.01% ≤ A ≤ 0.4%, and H1 satisfies: 20μm ≤ H1 ≤ 80μm.

2. The electrode assembly according to claim 1, characterized in that: The electrode plate and the separator are wound around multiple turns to form a flat electrode body. The electrode body includes a straight part and two corner parts. The two corner parts are respectively disposed at opposite ends of the straight part, and the corner parts have the first protrusions.

3. The electrode assembly according to claim 1, characterized in that: The electrode assembly satisfies at least one of the following conditions: (1) A satisfies: 0.01% ≤ A ≤ 0.10%, and H1 satisfies: 20μm ≤ H1 ≤ 40μm; (2) A satisfies: 0.10% < A ≤ 0.20%, and H1 satisfies: 40μm < H1 ≤ 60μm; (3) A satisfies: 0.20% < A ≤ 0.40%, and H1 satisfies: 60μm < H1 ≤ 80μm.

4. The battery according to claim 1, wherein The silicone is selected from at least one of methyl silicone resin, phenyl silicone resin, vinyl silicone resin, and silicone rubber; The fatty acid salt is selected from at least one of aluminum stearate, magnesium stearate, aluminum isooctanoate, and magnesium isooctanoate; The quaternary ammonium salt is selected from at least one of long-chain quaternary ammonium salts, short-chain quaternary ammonium salts, aliphatic quaternary ammonium salts, and aromatic quaternary ammonium salts.

5. The electrode assembly according to claim 1, characterized in that: The active material layer includes a first binder. Based on the total weight of the active material layer, the weight percentage content of the first binder is B; the electrode assembly satisfies at least one of the following conditions: (1) B satisfies: 0.8% ≤ B ≤ 1.6%, and H1 satisfies: 20μm ≤ H1 ≤ 40μm; (2) B satisfies: 1.6% < B ≤ 2.4%, and H1 satisfies: 40μm < H1 ≤ 80μm.

6. The electrode assembly according to claim 4, characterized in that: The first binder is selected from at least one of polyvinylidene fluoride, polyvinyl fluoride, polyvinyl alcohol, polystyrene, styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, polyvinyl acetate, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, and polytetrafluoroethylene; 7. The electrode assembly according to claim 1, characterized in that: The compacted density of the active material layer is ρ,3.6 g / cm 3 ≤ρ≤4.35g / cm 3 .

8. The electrode assembly according to claim 1, characterized in that: The electrode plate further includes a bottom coating disposed between the active material layer and the current collector. The bottom coating includes a bottom coating material selected from at least one of inorganic oxides and carbon-containing materials; The unit bottom coating weight of the bottom coating is η; the electrode assembly satisfies at least one of the following conditions: (1) η satisfies: 0.5mg / 1540.25mm 2 ≤η≤2.0mg / 1540.25mm 2 , H1 satisfies: 20μm≤H1≤40μm; (2) η satisfies: 2.0 mg / 1540.25 mm 2 ≤η≤4.0mg / 1540.25mm 2 , H1 meets: 40μm <H1≤80μm。 9. The electrode assembly according to claim 2, wherein The straight part has a second protrusion formed by the protrusion of another part of the current collector and another part of the active material layer toward the same side of the electrode plate; The height of the second convex portion is H2, 5 μm≤H2≤40 μm.

10. The electrode assembly according to claim 9, characterized in that: The radius of the inner surface of the first convex portion is R1, and the radius of the inner surface of the second convex portion is R2, R1=R2, 0.3mm≤R2≤10.0mm.

11. The electrode assembly according to claim 2, characterized in that: The straight portion has a first thickness L1 in the first direction; The two corner portions are arranged at opposite ends of the straight portion in a second direction perpendicular to the first direction, and the corner portions have a second thickness L2 in the second direction; Each circle of the pole piece comprises two straight sections arranged opposite to each other along the first direction, and two corner sections arranged at both ends of the straight section along the second direction; The pole piece has a tail end arranged corresponding to the straight segment of the pole piece of the outermost circle, and all the straight segments and the tail end stacked in the first direction form the straight portion; the first thickness L1 is the thickness of the straight portion passing the tail end in the first direction; all the corner segments located on the same side of the straight segment in the second direction form a corner portion, and the second thickness L2 is the thickness of the corner portion passing the midpoint of the line connecting the two ends of one of the innermost corner segments in the second direction; the electrode assembly satisfies at least one of the following conditions: (1) The number of windings of the pole piece of the electrode body is an even number, and L1 and L2 satisfy: 1.5≤L1 / L2≤2.2; or, (2) The number of winding turns of the pole piece of the electrode body is an odd number, and L1 and L2 satisfy: 1.5≤L1 / L2≤2.

4.

12. The electrode assembly according to claim 11, characterized in that: 1mm≤L1≤20mm, 0.5mm≤L2≤10mm.

13. A battery, characterized in that: include: shell; and, The electrode assembly according to any one of claims 1 to 12, wherein the electrode assembly is disposed in the inner space of the housing.

Citation Information

Patent Citations

  • Positive electrode slurry, positive electrode plate, battery cell, battery monomer, battery and electric device

    CN115832277A

  • Electrode assembly, battery, battery pack and electric equipment

    CN117199240A

  • Lithium ion secondary battery

    JP2013084454A

  • Secondary battery and electronic apparatus

    WO2024159521A1

Cited By

  • Battery and electric device

    CN120165038A

  • Battery and electric apparatus

    EP4815094A1

  • Electrode assembly and battery

    WO2026118601A1